Teaching Competencies in Education for Sustainable Development: A Study from Action Research - Aldaz Herrera, Nelson Marcelo (2023)
The objective of the research was to improve in a participatory way the teaching competencies in education for sustainable development (ESD) in an educational institution in Ecuador. The study was conducted based on the Rounder Sense of Purpose competency framework (Vare, 2018). Under the qualitative approach and under action research, we worked with eleven participants, with whom interviews and focus groups were conducted. As a consequence, in the diagnostic phase, the management, competencies and teaching practices in ESD were analyzed. From there, eight competencies were selected for the implementation of a training program. The program was executed and finally the evaluation was carried out, reflecting on the entire process. The results made it possible to determine the usefulness of the teaching skills training program for ESD, which stands out because it was well received in the educational community, and can also be replicated by other educational institutions.